Evaluating Motorcyclists’ Safe Riding Competencies: Integrating Hazard Perception, Theory, and Road Tests - M.K.A. Ibrahim; A.A. Ab Rashid; A. Hamzah; A. Awang; S.Z. Ishak (Journal of the Society of Automotive Engineers Malaysia, 2025)
This study presents a novel approach to evaluating motorcyclists’ safe riding competence through a comprehensive assessment framework. Participants were 31 consented courier riders aged 19 to 46 years (M = 29.9, SD = 7.43, 99% male) recruited through a road safety awareness program. A 100-cc motorcycle was fitted with a data acquisition system to record the motorcycle speeds and location, braking and turn signals data, and video images. The participants were asked to ride the instrumented motorcycle on a 6.5 km predefined route, which included riding in commercial areas, residential areas, town areas, and a section of a multi-lane highway. The participants also answered 32 safe riding theoretical questions and sat for a video-based hazard perception test. Results indicate that the developed instrumentation and scoring methodology are both suitable and replicable for evaluating motorcyclists’ safe riding competencies in real-world conditions. Notably, the assessment framework successfully differentiated various skill levels among participants, highlighting its discriminative power. Findings emphasize the necessity for targeted interventions to enhance higher-order riding skills, particularly in areas such as hazard perception and response. Given the high incidence of motorcycle fatalities and persistent road safety challenges, the research proposes a paradigm shift in approach: integration of more robust and comprehensive competency training and assessments in both licensing processes and post-license safety programs.